Cantharidin suppresses gastric cancer cell migration/invasion by inhibiting the PI3K/Akt signaling pathway via CCAT1. (1st February 2020) - Song, Mengyun; Wang, Xianfei; Luo, Yajun; Liu, Zilin; Tan, Wang; Ye, Pengcheng; Fu, Zhiming; Lu, Fei; Xiang, Wanping; Tang, Linghan; Yao, Lin; Nie, Yuqiang; et al.
Abstract: Cantharidin (CTD) is a traditional Chinese medicine that shows an anticancer effects in multiple types of cancer cells. However, the mechanism of CTD anti-cancer function in gastric cancer (GC) is still unclear. The aim of the present study was to investigate the underlying mechanism that CTD inhibits proliferation and migration through suppression of the PI3K/Akt signaling. CTD induced GC cell apoptosis and inhibited metastasis measured by CCK8 assays as well as wound healing assays and transwell assays. Mechanistic investigations suggested that CTD modulated the PI3K/Akt signaling via western-blot and quantitative q-PCR. In addition, we identified and confirmed CCAT1 as a novel direct target of CTD inhibited PI3K/AKt signaling expression. In conclusion, our results provide new point into the critical role of CTD in suppressing PI3K/Akt signaling via down-regulation of CCAT1, resulting in suppression GC cell growth and migration/invasion. Highlights: Cantharidin suppressed MGC803 and BGC823 cell metastasis by inhibiting PI3K/Akt signal pathway in vitro. Down-regulated CCAT1 by cantharidin may inhibit gastric cancer metastasis. CCAT1 may regulate PI3K/Akt signal pathway in gastric cancer cell.